Moore-paradoxical Assertion and Fully Conscious Belief - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2010)
Sidney Shoemaker (1995) has given an influential explanation of the absurdity of Moore-paradoxical belief in terms of conscious belief. Here I offer a novel account of the absurdity of Moore-paradoxical assertion in terms of an interlocutor’s fully conscious beliefs. This account starts with an original argument for the principle that fully conscious belief collects over conjunction. The argument is premised on the synchronic unity of consciousness and the transparency of belief.